Contemporary Malaysian consumer culture and the creative role of experiential space: reinterpreting sale and promotional advertising through installation - Mohd Fauzi Sedon (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Our consumer spaces are filled with extensive ranges of sale promotions of different products in a variety of prices that play a significant role in stimulating our senses. These sale promotions play a prominent role in the consumer’s decision to purchase goods and services. Repetition and similarity, difference and variation are the characteristics of this mass culture; they provoke a response and act as a catalyst for communication. These aspects of advertising stimulate our visual experience, affect our moods and emotions, and create the illusion of values and choices. This research project investigated the aesthetics of Malaysian consumer culture through exploration of the use of visual images based on the principle of repetition and variation (similarity and difference).The key artists within the research context were Andy Warhol and Allan McCollum, with their method of mass production and the use of popular mass produced images; and Andreas Gursky who represented consumer obsession and desire through shopping activities. The project established correlations between repetition, similarity and difference as they contribute to the variety of visual messages in advertising. It also contributed to the field of installation art by creating experiential environments that could evoke complex multi-sensory responses to the colours and images of advertising and significantly stimulate temptations and pleasures of the retail environment.